"Negative" characters in the novels of Charlotte Brontë - Steinbauerová, Andrea (Univerzita Pardubice, 2012)
This bachelor paper is focused on two novels written by Charlotte Brontë. These two novels are Jane Eyre and The Professor. The aim of the paper is to find out some "negative" characters in these two novels. Then these "negative" characters are compared with some aspects of the Victorian period. The paper mentions some aspects and values of the Victorian period, author's biography and her style of writing, a description of "negative" characters and some aspects of the Victorian period appearing in two novels. This work also shows how Charlotte Brontë used her experience in her novels, and how "negative" characters were punished.
"Negativní" postavy v románech Charlotty Brontëové
Keywords: Brontë, Charlotte; viktoriánská doba; negativní postavy; viktoriánské aspekty; viktoriánské hodnoty; victorian period; negative characters; victorian aspects; victorian values